Effect of a prepartum and postpartum, complex interdisciplinary lifestyle and psychosocial intervention on metabolic and mental health outcomes in women with gestational diabetes mellitus (the MySweetheart trial): randomised, single centred, blinded, controlled trial - Umberto Simeoni; Antje Horsch; Arnaud Chiolero; Yvan Vial; Nicole Sekarski; Jardena J Puder; Pascal Bovet; Yvan Mivelaz; Adina Mihaela Epure; Bobby Stuijfzand; Leah Gilbert; Stefano Lanzi; et al. (BMJ Medicine)
Objective To test the effect of a complex, interdisciplinary, lifestyle and psychosocial intervention on metabolic and mental health outcomes in women with gestational diabetes mellitus during pregnancy and in the post partum.Design Single centred, single blinded, randomised, controlled trial (the MySweetheart trial).Setting Lausanne University Hospital, Switzerland, from 2 September 2016 to 25 October 2021.Participants 211 women aged at least 18 years with a diagnosis of gestational diabetes mellitus at 24-32 gestational weeks were randomly assigned (1:1) to the intervention (n=105) or to usual care (n=106).Interventions In addition to a comparator based on active guidelines for prepartum and postpartum usual care, the intervention consisted of four individual lifestyle visits during pregnancy and four interdisciplinary visits in the postpartum group, a peer support group workshop in pregnancy and post partum, and a bimonthly lifestyle coach support through telemedicine. The intervention focused on tailored behavioural and psychosocial strategies to improve diet, physical activity, mental health, social support, and adherence to gestational weight gain during pregnancy and weight retention recommendations.Main outcome measures Primary outcomes were between-group differences in the decrease in maternal weight and depression symptom scores between baseline and one year post partum. Secondary outcomes included changes in total and central body fat, anxiety, wellbeing, glycaemic parameters (homeostatic model assessment for insulin resistance (known as HOMA-IR) and Matsuda indices), aerobic fitness (maximal oxygen uptake), gestational weight gain, and weight retention. Assessors were blinded to primary and secondary outcomes.Results 84 (80%) of 105 women in the intervention and 95 (90%) of 106 in the usual care completed the study. There was not enough evidence of a difference in the decrease in weight (mean difference –0.38 kg (95% confidence interval –2.08 to 1.30)) or depression scores (–0.67 (–1.84 to 0.49)). The intervention led to an increase in fat-free mass (0.02 kg (0.01 to 0.03)). The intervention also decreased gestational weight gain since the first gestational diabetes mellitus visit (–1.20 kg (–2.14 to –0.26)) and weekly weight gain throughout the entire pregnancy (–0.14 kg (–0.25 to –0.03)), and led to a higher proportion of women without weight retention at one year post partum (34.1% (28/82) v 20.8% (20/96), P=0.034).Conclusions Compared with active usual care based on guidelines, there was not enough evidence to conclude that the intervention led to decrease in weight or depression symptoms. However, the intervention decreased gestational weight gain and increased the proportion of women without weight retention.Trial registration Clinicaltrials.gov NCT02890693.